MENINGKATKAN HASIL BELAJAR IPA MELALUI MEDIA AUDIO VISUAL DI KELAS IV SDN MANGGARAI 09 PAGI JAKARTA SELATAN - Ramadhani, Sulistyani Puteri (Universitas Islam Negeri Alauddin Makassar, 2020)
The purpose of this classroom action research is to improve the science learning outcomes of human body skeleton material through audio-visual media in grade IV SDN Manggarai 09 South Jakarta. This study uses a cycle model from Stephen Kemmis and MC. Taggart. The research was carried out through the stages of recording, implementing actions, observing and reflecting. The results obtained from this study were an increase in science learning outcomes in grade IV SDN Manggarai 09 South Jakarta. In the first cycle the student learning outcomes were 65%. In cycle II, 75% of student learning outcomes have achieved the desired results. The implication of the results of this study is that using audio-visual media can be used as a means to improve science learning outcomes of human body frame material for grade IV elementary schools.